PENGARUH CURRENT RATIO DAN DEBT TO EQUITY RATIO TERHADAP NET PROFIT MARGIN PADA PT JAPFA COMFEED INDONESIA - Nurwita Nurwita; Eka Rahim; Fitri Konefi (Inovasi, 2022)
This study aims to analyze the effect of the variables Current Ratio, Debt to Equity Ratio, Net Profit Margin at PT Japfa Comfeed Indonesia Tbk 2012-2021. This type of quantitative research, quantitative research is research that does not focus too much on the depth of the data, the important thing is to be able to record as much data as possible from a large population, even though the research population is large but can easily be analyzed either through statistical or computer formulas so that solving research problems it is dominated by statistics. In this study the authors chose the research location at PT Japfa Comfeed Indonesia (JPFA) Tbk, the company has been listed on the Indonesia Stock Exchange. PT. Japfa Comfeed Indonesia (JPFA) is an agri-food company. Its core activities include the manufacture of animal feed, chicken farming, poultry processing and aquaculture. The company started commercial operations in January 1971. The research method used is quantitative and uses statistical analysis and financial ratios. This research was carried out in stages starting from preliminary studies, preparing proposals, collecting and collecting data, to processing data. Results of this Research.Keywords: Current Ratio, Debt to Equity Ratio, Net Profit Margin